Pengaruh Distribusi Produk dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan (Study Kasus PT. Daya Muda Agung Cirebon untuk Penjualan Produk Mahakam) - Mohamad Fikhan Primananda Kamilrizka; Pebi Kurniawan; Tedi Kustandi (INDO PUBLISHING, 2025)
This study aims to determine the influence of Product Distribution and Service Quality on Customer Satisfaction. The research method used is quantitative. The population in this study is all 71 consumers of Mahakam products at PT. Daya Muda Agung Cirebon. The sample was determined using a census/total sampling method, and primary data was collected through questionnaires. The research variables consist of Product Distribution and Service Quality as independent variables and Customer Satisfaction as the dependent variable. Data analysis was performed using SPSS 22. The results show that Product Distribution has a positive and significant influence on Customer Satisfaction, Service Quality has a positive and significant influence on Customer Satisfaction, and Product Distribution and Service Quality simultaneously have a positive and significant influence on Customer Satisfaction